2017
DOI: 10.1371/journal.pone.0172556
|View full text |Cite
|
Sign up to set email alerts
|

A novel flexible microfluidic meshwork to reduce fibrosis in glaucoma surgery

Abstract: Purpose/RelevanceFibrosis and hence capsule formation around the glaucoma implants are the main reasons for glaucoma implant failure. To address these issues, we designed a microfluidic meshwork and tested its biocompatibility in a rabbit eye model. The amount of fibrosis elicited by the microfluidic meshwork was compared to the amount elicited by the plate of conventional glaucoma drainage device.MethodsSix eyes from 3 New Zealand albino rabbits were randomized to receive either the novel microfluidic meshwor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 37 publications
0
11
0
1
Order By: Relevance
“…First, the number of rabbits used in this study was relatively small. Nevertheless, we assume that even a small population is enough for a study for introducing a novel material, such as the previous study using three rabbits to test the biocompatibility of microfluidic meshwork in Ahmed glaucoma valve surgery [ 23 ]. Second, this was a short-term study involving a 4-week observation period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the number of rabbits used in this study was relatively small. Nevertheless, we assume that even a small population is enough for a study for introducing a novel material, such as the previous study using three rabbits to test the biocompatibility of microfluidic meshwork in Ahmed glaucoma valve surgery [ 23 ]. Second, this was a short-term study involving a 4-week observation period.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have proposed different modifications to glaucoma drainage devices. The novel devices include an adjustable glaucoma device [ 19 ], a device delivering cyclosporine A [ 20 ] or MMC [ 21 ] for a certain period, and a device that contains a plate made of polymethyl methacrylate [ 22 ], or a plate replaced with microfluidic meshwork [ 23 ]. To our knowledge, this is the first preliminary study to demonstrate the use of a novel coating material for fibrosis inhibition in glaucoma implant surgery.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the appropriate choice of materials as well as the architecture of the GDDs can affect and reduce the postoperative development of fibrosis and scar formation [13,18,19]. A flexible microfluidic stent meshwork implanted in the subconjunctival space with channel sizes of cellular dimensions has demonstrated significantly less fibrosis development than the AGV PF7 in animal models [18].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the appropriate choice of materials as well as the architecture of the GDDs can affect and reduce the postoperative development of fibrosis and scar formation [13,18,19]. A flexible microfluidic stent meshwork implanted in the subconjunctival space with channel sizes of cellular dimensions has demonstrated significantly less fibrosis development than the AGV PF7 in animal models [18]. Although the basic mechanisms for fibrotic response and capsule formation around glaucoma drainage devices are not clearly understood, Amoozgar et al suggested that two implant-specific factors give rise to tissue reactions: (1) mechanical stress may develop at the interface between the tissue and the implant (e.g., due to a mismatch of mechanical properties) and (2) the implant disrupts the cellular and vascular system of the tissue [18].…”
Section: Introductionmentioning
confidence: 99%
“…Various methods have been used to halt the fibrosis formation, including the creation of a drug-coated device [ 5 , 6 ], intraoperative or postoperative anti-metabolite [ 7 , 8 ], subtenon steroid injection [ 9 ], and early start of aqueous suppressants [ 10 ]. Furthermore, modification of GDI’s material or design has always been tried [ 3 , 11 ]. Regarding the design, most GDI consists of a semirigid tube and a rigid and large reservoir.…”
Section: Introductionmentioning
confidence: 99%